PROTOTIPE SISTEM MONITORING PV-WIND DENGAN MENGGUNAKAN ATMEGA328 DAN RASPBERRY PI - Safari, Mohamad Ibnu (Journal of Digital Ecosystem for Natural Sustainability, 2021)
The depletion of petroleum reserves causes the opportunity for the use of renewable energy in the future to be very wide open, both in terms of energy needs at the industrial and personal level / BIPV (Building-Integrated Photovoltaic), namely housing that is integrated with renewable energy. It takes a monitoring system that is able to provide information data about the energy generated from the hybrid system (photovoltaics and wind turbines) online so that it can be monitored wherever and whenever. The expensive equipment to build a renewable energy system and the required information system will certainly be very burdensome for residential-scale renewable energy users (BIPV). The use of open source products and inexpensive equipment is an alternative to reduce costs. Using the 328 controller module as a data acquisition compatible with arduino IDE and rapsberry pi as a gateway using the debian linux operating system. The equipment communicates with each other wirelessly using a radio receiver, then the resulting data is displayed online using a cms dashboard so that it can be monitored wherever and whenever. The system used is open source (free) (arduino IDE, Linux debian, dashboard cms) so this monitoring system is cheap in terms of information systems.